Emotional intelligence, organizational justice and work outcomes - Micheal James Mustafa; Claudia Vinsent; Siti Khadijah Zainal Badri (Organization Management Journal (OMJ), 2023)
Purpose This study aims to explore the associations between emotional intelligence (EI), organizational justice (OJ) perceptions and work outcomes. The study proposes a model where EI is linked to job satisfaction and turnover intentions through the three dimensions of organizational justice. Design/methodology/approach In all, 556 employees in the Malaysian service sector were used as samples for this study. Analysis was performed using SPSS and AMOS structural equation modelling (SEM) path analysis to test the study's hypotheses. Findings Results indicate that EI had a significant direct effect on all organizational justice sub-dimensions (distributive, procedural and interactional justice) as well as on job satisfaction and turnover intentions. However, only distributive justice was found to partially mediate the relationship between EI, job satisfaction and turnover intentions. Originality/value This study provides further insights into the mechanisms through which trait EI impacts service sector employee workplace attitudes. It also investigates the role of trait EI in deciphering why employees may differ in their OJ perceptions and deepens understanding of the discrete roles that organizational justice sub-dimensions perform.
Keywords: 650; Emotional intelligence; Job satisfaction; Malaysia; Organizational justice perceptions; Turnover intention